2022
DOI: 10.3389/fonc.2021.807040
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Knosp, Revised-Knosp, and Hardy–Wilson Classifications for the Prediction of Surgical Outcomes in the Endoscopic Endonasal Surgery of Pituitary Adenomas: Study of 228 Cases

Abstract: PurposeTo evaluate which radiological classification, Knosp, revised-Knosp, or Hardy–Wilson classification, is better for the prediction of surgical outcomes in the endoscopic endonasal transsphenoidal (EET) surgery of pituitary adenomas (PAs).MethodsThis is a retrospective study of patients with PAs who underwent EET PA resection for the first time between January 2009 and December 2020. Radiological cavernous sinus invasiveness was defined as a Knosp or revised-Knosp grade >2 or a grade E in the Hardy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The Knosp classification scheme for cavernous sinus invasion by pituitary lesions is an example of an attempt to create clinically meaningful categories of anatomical involvement, which has been shown to be related to the extent of surgical resection achieved 27 . Table 3 lists common skull base lesions and the anatomical classification scales that attempt to describe them with concise uniform scoring systems.…”
Section: Building Consensusmentioning
confidence: 99%
“…The Knosp classification scheme for cavernous sinus invasion by pituitary lesions is an example of an attempt to create clinically meaningful categories of anatomical involvement, which has been shown to be related to the extent of surgical resection achieved 27 . Table 3 lists common skull base lesions and the anatomical classification scales that attempt to describe them with concise uniform scoring systems.…”
Section: Building Consensusmentioning
confidence: 99%
“…Marta et al. reported that Knosp and revised-Knosp classification showed good diagnostic accuracy in predicting surgical cure (AUC, 0.820), whereas Hardy classification lacked practicality in this purpose (AUC, 0.654) ( 22 ), which may indicate that the main prognostic factor was CSI ( 24 ). In an 8-year, retrospective, multicenter, cohort study that included 410 patients, Trouillas et al.…”
Section: Discussionmentioning
confidence: 99%
“…Knosp grade can reflect parasellar extension of the tumor. The Hardy–Wilson classification ( 10 ) was used for the assessment of suprasellar extension grades and sellar floor erosion grades ( Figures 2 , 3 ). It is important to point out that since Hardy D and E grades reflect parasellar extension, we only used Hardy 0–C grades for the evaluation of suprasellar extension grade.…”
Section: Methodsmentioning
confidence: 99%